Perinatal outcomes after a prenatal diagnosis of a fetal copy number variant: a retrospective population-based cohort study - Cecilia Pynaker; Jacqui McCoy; Jane Halliday; Sharon Lewis; David J. Amor; Susan P. Walker; Lisa Hui; On behalf of the PALM cohort study group (BMC, 2024)
Abstract Background There are no established guidelines for the follow up of infants born after a prenatal diagnosis of a genomic copy number variant (CNV), despite their increased risk of developmental issues. The aims of this study were (i) to determine the perinatal outcomes of fetuses diagnosed with and without a CNV, and (ii) to establish a population-based paediatric cohort for long term developmental follow up. Methods An Australian state-wide research database was screened for pregnant individuals who had a prenatal chromosomal microarray (CMA) between 2013-2019 inclusive. Following linkage to laboratory records and clinical referrer details, hospital records were manually reviewed for study eligibility. Eligible participants were mother-child pairs where the pregnancy resulted in a livebirth, the mother was able to provide informed consent in English (did not require a translator) and the mother was the primary caregiver for the child at hospital discharge after birth. Research invitations were sent by registered post at an average of six years after the prenatal diagnostic test. Statistical analysis was performed in Stata17. Results Of 1832 prenatal records examined, 1364 (74.5%) mother-child pairs were eligible for recruitment into the follow up cohort. Of the 468 ineligible, 282 (60.3%) had 'no live pregnancy outcome' (209 terminations of pregnancy (TOP) and 73 miscarriages, stillbirths, and infant deaths), 157 (33.5%) required a translator, and 29 (6.2%) were excluded for other reasons. TOP rates varied by the type of fetal CNV detected: 49.3% (109/221) for pathogenic CNVs, 18.2% (58/319) for variants of uncertain significance and 3.3% (42/1292) where no clinically significant CNV was reported on CMA. Almost 77% of invitation letters were successfully delivered (1047/1364), and the subsequent participation rate in the follow up cohort was 19.2% (201/1047). Conclusions This study provides Australia's first population-based data on perinatal outcomes following prenatal diagnostic testing with CMA. The relatively high rates of pregnancy loss for those with a prenatal diagnosis of a CNV presented a challenge for establishing a paediatric cohort to examine long term outcomes. Recruiting a mother-child cohort via prenatal ascertainment is a complex and resource-intensive process, but an important step in understanding the impact of a CNV diagnosis in pregnancy and beyond. Trial registration ACTRN12620000446965p; Registered on April 6, 2020.